CORRELATION OF LYMPHOCYTE-MONOCYTE RATIO AND MORTALITY OF COVID-19 INTENSIVE CARE UNIT PATIENTS: PRELIMINARY STUDY - Muhammad Fadhil Naufal; Ade Susanti; Fairuz Quzwain (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
Background: The world faces a pandemic caused byÂ  Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-Cov-2). Because of the limitations as a developing country, Indonesia needs to do its activities efficiently in time, money, and human resource. This research aims to accurately determine a concrete mortality predictor to predict the patients' mortality. One of the mortality predictors is the lymphocyte-monocyte ratio (LMR). Method: This research is observational analytic research using a cross-sectional study method. Data obtained from the Medical Record & Casemix Room of RSUD Raden Mattaher. Results: Out of 115 samples, most patients were male (65 patients). The patients' age group was mainly younger than 65 (79%). The most common comorbidity was diabetes mellitus (43 patients). The correlation between LMR and mortality rate to be weak with the following results: Pearson coefficient(p=0.045), gamma coefficient (P=0.325), Somers' D test (P=0.167), odds ratio (1.833), AUC (58%), specificity (58%), sensitivity (56%), and intersection point (1,79). Conclusions: There is a weak correlation between LMR and the mortality rate of COVID-19 patients in RSUD Raden Mattaher. Keywords: Characteristics of COVID-19 patients, Comorbidity of COVID-19 patients, LMR (Lymphocyte-monocyte ratio), a Mortality rate of COVID-19 patients